Astaxanthin mitigates diabetic cardiomyopathy and nephropathy in HF/HFr/STZ diabetic rats via modulating NOX4, fractalkine, Nrf2, and AP-1 pathways - Nesma M.E. Abo El-Nasr; Yosra A. Hussien; Marawan Abd El-Baset; Marwa E. Shabana; Dalia O. Saleh (Scientific Reports)
Abstract This study investigated the effects of astaxanthin (ASTA) on diabetic cardiomyopathy (DCM) and nephropathy (DN) in rats. Type 2 diabetes was induced through a high-fat/high-fructose (HF/HFr) diet followed by a sub-diabetogenic dose streptozotocin injection. Diabetic rats were treated with ASTA at a dose of 100 mg/kg for four weeks. Serum markers of renal and cardiac function, oxidative stress parameters, and electrocardiographic (ECG) measurements were assessed. Diabetic control rats exhibited significant impairment in renal and cardiac functions, heightened oxidative stress, and altered ECG parameters. Treatment with ASTA (100 mg/kg) markedly improved these conditions, proven by reduction in serum urea, creatinine, cardiac creatine phosphokinase-MB (CK-MB), and LDH levels. Additionally, oxidative stress markers such as MDA, GSH, SOD, and NOX4 were restored in both heart and kidney tissues. Furthermore, ASTA was able to increase the cardiac and renal Fractalkine chemokine as well as attenuate the elevated Nrf2 and AP-1. ECG abnormalities were partially reversed, with enhancements in the QTc interval and ST segment height. The histopathological examination of cardiac and renal tissues confirmed these results. Finally, the forementioned promising observations suggest that ASTA may offer therapeutic potential in mitigating DCM and DN via modulation of NOX4, Fractalkine, Nrf2, and AP-1 Pathway, warranting further research into its mechanisms and clinical applicability.